Managing the manufacturing–R&D interface in the process industries. (21st May 2013) - Storm, Per; Lager, Thomas; Samuelsson, Peter; Lager, Thomas; Blanco, Sylvie
<x xml:space="preserve">Abstract</x> In the perspective of value creation and capture, firms in the future must not only be excellent in developing commodities or innovative functional products; they must also be able to manufacture them in a competitive cost structure within the framework of a proper business model. Deploying a conceptual model of the material transformation system in the process industries, the relationship between firms' manufacturing and innovation activities has been explored in three case studies representing the food, mineral and steel industries. Using the methodology of Quality Function Deployment, each firm's position on the model structure has been condensed into a matrix relating the manufacturing system's characterizing variables to the firm's raw material innovation, innovation of process technology and product innovation. The importance of the area of process innovation stands out in all these firms, and among the individual variables 'product flexibility' ranked highest in all of them. It is recommended that in the development of corporate innovation strategies, the product–market perspective ought to be supplemented by a process–manufacturing perspective. Combining the information from both perspectives and striking a proper balance ought to be beneficial in overbridging the manufacturing–R&D interface.